Strategi Pengembangan Bank Syariah di Daerah Otonomi Gunungsitoli Nias - Nisrina Hulu (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2019)
The purpose of this study was to determine the development strategy of Islamic banks in the Gunungsitoli autonomous region in Nias, to determine opportunities for the establishment of sharia business units at commercial banks in Gunungsitoli, to find out the challenges of establishing sharia business units at commercial banks in Gunungsitoli. The research approach used in this study is a qualitative descriptive approach. The results of this study will not only be analyzed qualitatively descriptive but the author also uses a SWOT analysis. SWOT analysis is the systematic identification of various factors to formulate the corporate strategy of BRI banks and SUMUT banks. From the analysis, it was found that the development strategy of Islamic banks in the autonomous region of Gunungsitoli in Nias was based on the SWOT analysis, namely increasing promotion and socialization of Islamic bank products, which meant that increased promotion and outreach was a major force possessed in the development of Islamic Banks. Opportunities for the establishment of Islamic banks in the autonomous region of Gunungsitoli Nias, the results when viewed from the results of the SWOT analysis have considerable opportunities can be proven by the existence of the Law on Banking & Fatwa MUI, the existence of the MUI fatwa on usury, the most dominant factor in the score on the opportunity aspects shows that the existence of the Banking Act and MUI Fatwa can influence and encourage prospective customers to trust their funds in Islamic banks. The challenges in establishing Islamic banks in the autonomous region of Gunungsitoli Nias, namely the conventional system and other more developed financial institutions, make it a challenge for the development of Islamic banks in Gunungsitoli, Nias, and Islamic financial institutions are still not well established in the eyes of the community because of the people in Gunungsitoli, Nias